2020
DOI: 10.3324/haematol.2019.226126
|View full text |Cite
|
Sign up to set email alerts
|

HES1 and HES4 have non-redundant roles downstream of Notch during early human T-cell development

Abstract: In both mouse and human, Notch1 activation is the main initial driver to induce T-cell development in hematopoietic progenitor cells. The initiation of this developmental process coincides with Notch1-dependent repression of differentiation towards other hematopoietic lineages. Although well described in mice, the role of the individual Notch1 target genes during these hematopoietic developmental choices is still unclear in human, particularly for HES4 since no orthologous gene is present in the mouse. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Thus, copy number gains of HES4 may be a further mechanism for enforced NOTCH pathway activation in OAML. Although CEBP family members are mainly known for their function in myeloid cells, there are indications that CEBPB and CEBPD may have roles in B lineage malignancies [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, copy number gains of HES4 may be a further mechanism for enforced NOTCH pathway activation in OAML. Although CEBP family members are mainly known for their function in myeloid cells, there are indications that CEBPB and CEBPD may have roles in B lineage malignancies [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…HES4 showed gains in four of the cases. HES4 is a downstream target and effector of NOTCH activity [21]. CEBPB, which showed gains in four OAML, functions as transcription factor in myeloid cells, but it also has a pathogenetic role in multiple myelomas, and positively regulates BCL2 in B cells [22,23].…”
Section: Analysis Of Wgs Data For Cnvs Chromosomal Translocations Amentioning
confidence: 99%
“…Several studies showed that DNA methylation can alter the binding of CTCF to influence the 3D architecture of the genome (38)(39)(40). Therefore, we compared the genes downregulated by Decitabine in both PDX and T-ALL cell lines with gene expression in CTCF depleted acute leukemia (41).…”
Section: Cluster a Cpg Island Methylation Defines The Proliferative Hmentioning
confidence: 99%
“…For both genes, these types of mutations cause a gain of function, as the inhibitory C-terminal PEST domains are removed or otherwise inactivated. Copy number gains in the NOTCH target HES4 may be a further mechanism of enforced NOTCH pathway activity in OAMZL [ 51 , 100 ].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%